The impact of cybersecurity risk management on building digital trust and its impact on financial inclusion under financial technology (Al-Mostansiriyah journal for Arab and international studies, 2026)
AbstractThis research aims to analyze the impact of cybersecurity risk management on building digital trust and its reflection on financial inclusion through fintech in Iraqi banks. The study stems from the problem that escalating cyber risks may weaken users' trust in digital financial services, thus limiting their spread and affecting levels of financial inclusion, particularly in the dimensions of access, use, and quality. The descriptive results revealed that cybersecurity risk management is available at a high level, with significant improvements in prevention and updates, but weaknesses in learning from incidents and classifying them according to international standards. Digital trust was also found to be at a high level, driven by security and service effectiveness, but with a weakness in ethical commitment. Financial inclusion through fintech was found to be at a moderate level, specifically in terms of weak service quality. Correlation testing demonstrated strong and significant positive relationships between the three variables. The impact analysis showed that digital trust acts as a partial mediator between cybersecurity risk management and financial inclusion, meaning that risk management directly and indirectly enhances financial inclusion by strengthening digital trust. Accordingly, the study recommends enhancing institutional learning from incidents, developing transparency and ethical commitment, and improving the quality of digital services to support financial inclusion in the Iraqi banking environment.Keywords: cybersecurity risk management; digital trust; financial inclusion; financial technology; Iraqi banks.